Pengaturan Pengenaan Pajak Bumi dan Bangunan Terhadap Tanah Suku (Muk Reu Ginil) di Desa Duarato dan Desa Leowalu Kecamatan Lamaknen Kabupaten Belu - Deodatus Nafri Asa; Kotan Y. Stefanus; Rafael R. Tupen (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this research is to analyze the regulation of land and building tax imposition on tribal land (muk reu ginil) in Duarato Village and Leowalu Village, Lamaknen District, Belu Regency. This research is a normative juridical research that examines all regulations relating to Land and Building Tax and customary land, as well as the mechanism for collecting Land and Building Tax in Belu Regency, especially Duarato Village and Leowalu Village and is supported by empirical juridical research, namely interviews with the Village Head, Traditional Leaders, the Community and also Belu Regency Bapenda employees to find out the practice of imposing Land and Building Tax on tribal land (muk reu ginil) in Duarato Village and Leowalu Village which has been carried out. The results of the research show that until now there has been no specific regulation related to the imposition of Land and Building Tax on customary land or tribal land, either at the national level or at the regional level. The absence of regulations related to the imposition of PBB on tribal land does not make tribal land unrecognized by the Regional Government of Belu Regency. This is because tribal land in Belu Regency, especially Duarato Village and Leowalu Village, is taxed and as a form of recognition of tribal land, the name of the tribe of the taxpayer is also included in addition to the name of the taxpayer himself to show that the land cultivated by him is tribal land.